Effect of some Cultivation Factors and Extraction Methods on Terminalia Catappa L. Seed Oil - Le Hong Nguy; Ly Thi Minh Hien; Dong Thi Anh Dao (International Journal of Food Science)
Terminalia catappa L. is a common tropic tree for shade and ornament in many countries. Recently, Terminalia catappa L. seed oil has been considered as a new oleaginous seed for dietary and biofuel production. In this study, ripe Terminalia catappa L. fruits originated in Vietnam were collected and seed oil extracted. In our experiment conditions, the effect of tree location, tree age, and annual harvest time on seed weight and seed oil content was investigated. As results, the seeds at the eastern site of the ground obtained not only the biggest size (3.607 g) but also contained the highest oil mass percentage (56.38%). The suitable annual harvesting time for the good seed quality was from March to April. In addition, the Terminalia catappa L. seeds for oil extraction began being harvested in the fourth year with 55.88% oil content compared to 55.99% of the five and six-year-old and trees. After seed drying, the seed oil was extracted by five different methods including cold screw pressing, hot screw pressing, hydraulic pressing, and solvent extracting, and combining method (cold screw pressing then solvent extraction of oil cake). Among the physical methods, cold screw pressing observed the highest oil yield of 77.32%, and the good oil quality was obtained with low free fatty acid (0.550% oleic acid), low acid value (1.080 mg KOH/g oil), and low peroxide value (1.240 meq O2/kg oil). However, the combination of cold screw pressing and cake oil extracting by solvent increased the oil yield by 14.61%. The saponification values fluctuated between 196 to 197 mg KOH/g oil, while the iodine values were in the range of 77.00 and 79.89 g I2/kg oil.